Kesesuaian Akad dan Tantangan Implementasi Sharia Restricted Investment Account (SRIA): Studi Komparatif Indonesia dan Malaysia - Pandu Septa Nugraha; R Ahmad Qodratu (CV Kalimasada Group, 2026)
This study analyzes the business model of the Sharia Restricted Investment Account (SRIA) in the Indonesian Islamic banking sector, with a particular focus on the compliance of the mudharabah muqayyadah contract with Sharia principles and the challenges of its implementation following the issuance of the 2024 SRIA Implementation Guidelines by the Financial Services Authority (OJK). The research adopts a qualitative normative-conceptual approach through content analysis, comparative analysis, and critical analysis of relevant regulations, fatwas issued by the National Sharia Council–Indonesian Council of Ulama (DSN-MUI), standards issued by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and the Islamic Financial Services Board (IFSB), as well as SRIA implementation documents from Islamic banking institutions in Indonesia and Malaysia. The findings indicate that the mudharabah muqayyadah contractual structure underlying the SRIA is fundamentally consistent with the principles of fiqh al-mu'amalat and complies with the prohibitions of riba (usury), gharar (excessive uncertainty), and maysir (gambling). Moreover, it establishes a tripartite legal relationship among investors, Islamic banks, and financing recipients that more accurately reflects the principle of risk sharing than conventional deposit products. Nevertheless, its implementation continues to face significant challenges, including limited information transparency, inadequate investor protection, and low levels of customer literacy and market interest. This study proposes the Integrated Sharia Restricted Investment Account Development Framework (ISRIA Framework) as a conceptual model for SRIA development that integrates five key pillars: regulatory foundation, Sharia governance, real-sector integration, investor literacy, and sustainable innovation. These findings contribute theoretically to the advancement of Restricted Investment Account literature within Islamic finance and provide practical implications for regulators and the Islamic banking industry in strengthening a competitive and Sharia-compliant investment business model.